Doing things with games : social impact through play - Grace, Lindsay D. (Boca Raton, FL : CRC Press/Taylor & Francis Group, 2019)
"Lindsay Grace's Doing Things with Games: Social Impact Through Play provides a contemporary foundation in designing social impact games. It is structured in 3 parts: understanding, application, and implementation. This text serves as the ultimate guide to designing social impact games, particularly focused on the needs of, media professionals, indie game designers and college students. It serves as a guide for people looking to create social impact play, informed by heuristics in game design"--
No titles -- An overview of designing for social impact -- Engagement design and serious play -- Educational games -- Changing the body and mind -- Defining newsgames and its compliments -- Persuasive play -- Empathy games -- Designing for communities of play -- Human computation, community action and other social impact -- Prototyping, ethics and testing -- Thinking about implementation -- Implementation tools.
OCLC-licensed vendor bibliographic record.
Keywords: Games -- Social aspects; COMPUTERS / General; COMPUTERS / Computer Graphics / Game Programming & Design